Efficacy of purposeful educational workshop on nursing care - Aminoroaia, Mahin (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: This study aimed to define the efficacy of a nursing care educational workshop on nurses’ knowledge and attitude until 3 months after holding the workshop in psychiatric wards of educational hospitals in Isfahan. MATERIALS AND METHODS: This is a quasi-experimental study. The study population comprised all nurses working in psychiatric wards of Nour and Farabi hospitals in Isfahan in 2012. An educational workshop was held through educational sessions in the form of lectures and group discussion in the two above-mentioned hospitals. Nurses’ level of knowledge and attitude were investigated by a researcher-made questionnaire before, immediately after, and 3 months after intervention. Data were analyzed by descriptive statistical tests of repeated measures ANOVA and Bonferroni. RESULTS: A significant increase was observed in mean scores of nurses’ knowledge immediately after and 3 months after education compared to before education. Nurses’ knowledge mean scores increased from 59.2 ± 14.8 before education to 88.6 ± 8.4 immediately after and to 71 ± 9.8 3 months after (P ≤ 0.016). There was no significant difference in mean scores of nurses’ attitude in the three above-mentioned time points. CONCLUSION: Educational sessions notably affected the promotion of nurses’ knowledge. With regard to nurses’ satisfaction with the workshop that was held, designing and organizing educational workshops based on constant needs assessment is suggested for promotion of nursing cares.